Seasonal planning procedures to improve irrigation management performance: how Kirindi Oya experience can be transferred to NIRP schemes. Proceedings of the Workshop on Seasonal Planning Procedures to Improve Irrigation Management Performance: how Kirindi Oya experience of IIMI/ID can be transferred to NIRP schemes, held at the Irrigation Department, Colombo, Sri Lanka, on 16 May 1994 - Panabokke, Christopher R.; Haq, K.A.; Samarasekera, B.M.S. (International Irrigation Management Institute, 1997)
The worshop was to assess the Kirindi Oya experiences with respect to the different problems and successes relating to social and instituaional stratergies that were promoted at Kirindi Oya. It deals with the seasonal planing procedures to improve irrigation management performance emphasizing how the Kirindi Oya experiences of IIMI and the Irrigation Department can be trasferred to NIRP schemes.